SUpervised exercise-therapy and Patient Education Rehabilitation (SUPER) versus minimal intervention for young adults at risk of knee osteoarthritis after ACL reconstruction: SUPER-Knee randomised controlled trial protocol. Issue 1 (18th January 2023) - Culvenor, Adam G; West, Thomas J; Bruder, Andrea M; Scholes, Mark J; Barton, Christian J; Roos, Ewa M; Oei, Edwin; McPhail, Steven M; Souza, Richard B; Lee, Jusuk; Patterson, Brooke E; Girdwood, Michael A; et al.
Abstract : Introduction: Anterior cruciate ligament injury and reconstruction (ACLR) is often associated with pain, functional loss, poor quality of life and accelerated knee osteoarthritis development. The effectiveness of interventions to enhance outcomes for those at high risk of early-onset osteoarthritis is unknown. This study will investigate if SUpervised exercise-therapy and Patient Education Rehabilitation (SUPER) is superior to a minimal intervention control for improving pain, function and quality of life in young adults with ongoing symptoms following ACLR. Methods and analysis: The SUPER-Knee Study is a parallel-group, assessor-blinded, randomised controlled trial. Following baseline assessment, 184 participants aged 18–40 years and 9–36 months post-ACLR with ongoing symptoms will be randomly allocated to one of two treatment groups (1:1 ratio). Ongoing symptoms will be defined as a mean score of <80/100 from four Knee injury and Osteoarthritis Outcome Score (KOOS4 ) subscales covering pain, symptoms, function in sports and recreational activities and knee-related quality of life. Participants randomised to SUPER will receive a 4-month individualised, physiotherapist-supervised strengthening and neuromuscular programme with education. Participants randomised to minimal intervention (ie, control group) will receive a printed best-practice guide for completing neuromuscular and strengthening exercises following ACLR. The primary outcome will be change in the KOOS4 from baseline to 4 months with a secondary endpoint at 12 months. Secondary outcomes include change in individual KOOS subscale scores, patient-perceived improvement, health-related quality of life, kinesiophobia, physical activity, thigh muscle strength, knee function and knee cartilage morphology (ie, lesions, thickness) and composition (T2 mapping) on MRI. Blinded intention-to-treat analyses will be performed. Findings will also inform cost-effectiveness analyses. Ethics and dissemination: This study is approved by the La Trobe University and Alfred Hospital Ethics Committees. Results will be presented in peer-reviewed journals and at international conferences. Trial registration number: ACTRN12620001164987.